RE-DESIGN SISTEM KEMUDI KENDARAAN BIO-HYBRID OBHI-MEC UNUD DENGAN MENGGUNAKAN SINGLE TIE ROD - Markheshiwan, Kevin Daniel; Karohika, I Made Gatot; Widiyarta, I Made (Teknik Desain Mekanika, 2024)
Abstract Steering system on the Bio-Hybrid OBHI-Mec Unud vehicle has problem when being use where the driver feels diffficult when turning the steering wheel of the Bio-Hybrid OBHI-Mec Unud vehicle. The steering system currently installed uses 2 tie rods which are attached directly to the steering joint. In the research, testing was carried out on a new steering structure using 1 long tie rod as a replacement for 2 tie rods that connected to the steering joint and 1 short tie rod as a connector between the steering joint and the long tie rod. The test was do statically with a vehicle with 1 driver plus 2 passengers carried out on the ashpalt surface. Analysis was carried out on the moment value and also the force value produced when turning the steering handlebar. The results of this research using a single tie rod steering system succeeded in reducing the force and moment when turning the steering handlebar in a static condition by 37.12% which gave the effect of feeling lighter and easier when turning the steering wheel of the Bio-Hybrid OBHI-Mec Unud vehicle. Keywords: Tie rod steering, force, moment